Respostas

2014-06-18T18:56:56-03:00
Porque ?

para tornar a expressão o menor possivel

Simplifique a expressão : 3√2 - 2√18 + 3√72 = 15√2 

fatorar 18| 2                        72| 2
             9| 3                         36| 2
             3| 3                         18| 2
              1/                             9| 3
                                              3| 3
                                               1/


Observe as RAÍZES

√18 = √2.3.3 = √2.3²   = 3√2     elimina a  √  com o (²))

√72 =  √2.2.2.3.3  =  √2².2.3²  = 2.3 √2 = 6√2

vamos substituir

 3√2 - 2√18   + 3√72 = 15√2 

3√2 -  2.3√2  + 3.6√2 = 15√2
3√2 -   6√2    + 18√2  =  15√2     agora é só SOMAR

3√2 + 18√2 - 6√2      = 15√2
       21√2   - 6√2      = 15√2

            15√2            = 15√2